Sink or swim: Adversity- and growth-related experiences in Olympic swimming champions. (March 2015) - Howells, Karen; Fletcher, David
Abstract: Objective: To explore the adversity- and growth-related experiences of swimmers at the highest competitive level. Of particular interest was the transitional process that the swimmers progress through to positively transform their experiences. Design: Eight autobiographies of Olympic swimming champions were sampled and analyzed. Method: The books were written by four male and three female swimmers whose ages at the time of their Olympic swims ranged from 14 to 41 years ( M  = 23.39, SD  = 6.04). Informed by a narrative tradition, the autobiographies were subjected to a holistic analysis which involved scrutinizing the form of the structure and style of the narrative, and the content relating to the events and meanings described by the authors. Results: The swimmers perceived their adversity-related experiences to be traumatic and initially attempted to negotiate them by maintaining a state of normality through the development of an emotional and embodied relationship with water. This relationship involved the non-disclosure of traumatic adversities and the development of multiple identities. As these strategies eventually proved to be maladaptive and exposed the swimmers to further adversity, the dialog of the autobiographies typically shifted to a more quest-focused narrative with the swimmers seeking meaning in their experiences and looking to others for support. Adoption of these strategies was necessary for the swimmers to experience growth, which was identifiable through superior performance, enhanced relationships, spiritual awareness, and prosocial behavior. Conclusion: The findings provide broad support for theories of posttraumatic growth and suggest that assimilation processes may comprise initial phases of the transition between adversity and growth. We discuss a number of practical implications for psychologists and significant others involved with elite swimmers. Highlights: Eight autobiographies of Olympic swimming champions were sampled and analyzed. Swimmers perceived their adversity-related experiences to be traumatic. Swimmers went through a transitional process to positively transform their experiences. Growth involved superior performance, enhanced relationships, spiritual awareness, and prosocial behavior.